PERLINDUNGAN HUKUM ATAS HAK NORMATIF PENGEMUDI TRANSPORTASI ONLINE DITINJAU DARI STATUS KEMITRAAN KETENAGAKERJAAN - Najwa Ardelia Cahyarani; Viona Maylinda Sari; Panji Semangun; Aryo Apsa Wicaksono; Agus Septima Ridwan (JOURNAL OF LAW AND NATION, 2026)
The emergence of online transportation platforms such as Gojek has created a new legal relationship based on a partnership system that formally positions drivers as independent partners rather than employees. This study aims to analyze the legal standing of online transportation drivers within Indonesia's labor law framework and to formulate appropriate legal protections for drivers' normative rights amid the regulatory vacuum in the gig economy. The research employs a normative juridical method with statutory and analytical approaches through a literature study of applicable laws, standard partnership agreements, and labor law literature. The findings indicate that, in substance, the relationship between drivers and application platforms contains the elements of work, wages, and command as stipulated in Article 1 number 15 of Law Number 13 of 2003 on Manpower, making the partnership status imposed on drivers a form of corporate legal camouflage. The regulatory vacuum in the gig economy results in drivers losing normative rights such as minimum wage, religious holiday allowances, severance pay, and social security. Regulatory reform that explicitly recognizes the category of platform workers is urgently needed to ensure legal certainty and justice.